Handling sticky resin by stingless bees (Hymenoptera, Apidae) - Markus Gastauer; Lucio A. O. Campos; Dieter Wittmann (Revista Brasileira de Entomologia, 2011)
For their nest defense, stingless bees (Meliponini) collect plant resins which they stick on intruders like ants or cleptobiotic robber bees causing their immobilization. The aim of this article is to identify all parts of stingless bee workers contacting these sticky resins. Of special interest are those body parts with anti-adhesive properties to resin, where it can be removed without residues. For that, extensive behavioral observations during foraging flight, handling and application of the resin have been carried out. When handling the resin, all tarsi touch the resin while walking above it. For transportation from plants to the nest during foraging flight, the resin is packed to the corbicula via tarsi and basitarsi of front and middle legs. Once stuck to the resin or after the corbicula had been unloaded, the bee's legs have to be cleaned thoroughly. Only the tips of the mandibles, that form, cut and apply the sticky resin, seem to have at least temporarily resin-rejecting properties.